Reforming governance in the Israeli welfare state: The role of organizational settlements beyond the state in instituting change - Asa Maron (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2014)
Welfare state governance reforms are established by new constellations of actors and experimental organizational structures. This paper analyses two most similar cases of governance reforms in two welfare state domains: (1) services for children and teens at risk; and (2) employment services and social security benefits. It utilizes a comprehensive empirical study that surveys reform initiatives and the establishment of innovative governance coalitions formed in order to enable the recalibration of the Israeli welfare state to changing conditions. In both cases, preliminary deliberations of senior bureaucrats were able to establish change coalitions, which were vital in order to overcome bureaucratic stalemates that result from path-dependent administrative legacies. Notwithstanding, governance coalitions differ in their ability to institutionalize new governance configurations within the state: while the new configuration for governing services for at risk populations won political legitimacy and was instituted, the workfare governance configuration suffered from political illegitimacy and was ultimately abolished. By focusing on the organizational aspects of welfare state reform, the paper argues that tentative coalitions' potential to transform into legitimate and sustainable governance configurations depends on their ability to establish inclusive organizational settlements between agencies with different interests, beyond the bureaucratic structure of the state. – – Wohlfahrtsstaatliche Regierungsreformen werden wesentlich von neuen Akteurskonstellationen und experimentellen Organisationsstrukturen bestimmt. Das Arbeitspapier analysiert zwei sehr vergleichbare Regierungsreformen in zwei Politikfeldern des Israelischen Wohlfahrtsstaates: (1) Leistungen für gefährdete Kinder und Jugendliche sowie (2) Arbeitsvermittlung und Sozialleistungen. Dafür wird auf eine umfassende empirische Studie zurückgegriffen, die sowohl Reformanstöße als auch die Etablierung innovativer Regierungskonstellationen untersucht. Und zwar jene, die eine Anpassung des israelischen Wohlfahrtsstaates an sich ändernde Rahmenbedingungen ermöglichen. In beiden Fällen wurde die Bildung neuer Koalitionen durch Beratungen von Dienstälteren ermöglicht. Für die Überwindung des bürokratischen Stillstandes, der als Resultat vorangegangener verwaltungstechnischer Altlasten im Sinne der Pfadabhängigkeitstheorie verstanden werden kann, waren diese unerlässlich. Ungeachtet dessen unterscheiden sich Regierungskoalitionen in ihrer Fähigkeit, neue Regierungsstrukturen innerhalb des Staates zu errichten: Während die Neugestaltung von Staatsleistungen für prekäre Bevölkerungsteile an politischer Legitimität gewann und demnach institutionalisiert wurde, fehlte es den sogenannten Workfare-Leistungen an jener Legitimität, was schlussendlich zu deren Abbau führte. Mit Blick auf die Organisationsaspekte von Wohlfahrtsstaatsreformen argumentiert das Arbeitspapier, dass das Entwicklungspotenzial von vorläufigen Koalitionen hin zu legitimen und dauerhaften Regierungsstrukturen vor allem von deren Fähigkeit abhängig ist, inklusive Organisationsstrukturen zu schaffen, welche Ausgleiche zwischen verschiedenen Interessensgruppen fernab der bürokratischen Staatsstruktur ermöglichen.
Keywords: 300